2017
DOI: 10.1038/s41598-017-14444-3
|View full text |Cite
|
Sign up to set email alerts
|

Complement receptors C5aR1 and C5aR2 act differentially during the early immune response after bone fracture but are similarly involved in bone repair

Abstract: Severely injured patients frequently suffer compromised fracture healing because of systemic post-traumatic inflammation. An important trigger of the posttraumatic immune response is the complement anaphylatoxin C5a, which acts via two receptors, C5aR1 and C5aR2, expressed on immune and bone cells. The blockade of C5a-mediated inflammation during the early inflammatory phase was demonstrated to improve fracture healing after severe injury. However, the distinct roles of the two complement receptors C5aR1 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 49 publications
(86 reference statements)
3
55
0
Order By: Relevance
“…In a recent in vivo study, we demonstrated that the lack of C5aR1 or C5aR2 differentially affected bone cells and the early inflammatory phase of fracture healing. 8 Therefore, further studies are required, dissecting C5aR1from C5aR2-mediated effects in osteoblasts, to enable tailored C5a receptor-modulation under inflammatory bone conditions in future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent in vivo study, we demonstrated that the lack of C5aR1 or C5aR2 differentially affected bone cells and the early inflammatory phase of fracture healing. 8 Therefore, further studies are required, dissecting C5aR1from C5aR2-mediated effects in osteoblasts, to enable tailored C5a receptor-modulation under inflammatory bone conditions in future.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in osteoblasts C5a induces migration and expression of the inflammatory cytokines interleukin‐6 (IL‐6) and IL‐8, and receptor activator of nuclear factor kappa B ligand (RANKL), which is essential for osteoclast formation and activity . Moreover, C5aR1‐knockout (‐ko) mice display reduced osteoclast numbers and significantly increased bone mass, suggesting that C5a/C5aR1 signalling might regulate physiological bone turnover . The C5a/C5aR1 axis in bone cells might be particularly relevant under pathological conditions, because mice lacking C5aR1 are protected against arthritis, and C5aR1 activity has been linked to substantial bone loss in a periodontitis model .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, C5a activation is independent of C3 . Furthermore, recent work demonstrates that both C5a receptors, C5aR1 and C5aR2, are required for bone healing, particularly in cartilage‐to‐bone transition . Interestingly, this is in contrast to C5aR antagonists in polytrauma fracture healing, which has been shown to improve bone healing .…”
Section: Inflammatory Phase—inflammatory Cellsmentioning
confidence: 99%
“…39 Furthermore, recent work demonstrates that both C5a receptors, C5aR1 and C5aR2, are required for bone healing, particularly in cartilageto-bone transition. 40 Interestingly, this is in contrast to C5aR antagonists in polytrauma fracture healing, which has been shown to improve bone healing. 41 As many cell types involved in bone healing express complement receptors, including, inflammatory cells, osteoclasts, and osteoblasts, fully understanding the role of complement in bone healing will require temporal and cell-type specific allelic disruption.…”
mentioning
confidence: 99%